Application of Theoretical Solubility Calculations and Thermal and Spectroscopic Measurements to Guide the Processing of Triamcinolone Acetonide by Hot-Melt Extrusion - Pedro A. Granados; Idejan P. Gross; Patrícia Medeiros-Souza; Livia L. Sá-Barreto; Guilherme M. Gelfuso; Tais Gratieri; Marcilio Cunha-Filho (Pharmaceutics)
Background/Objectives: Triamcinolone acetonide (TA), a poorly water-soluble corticosteroid, presents formulation challenges due to limited membrane permeability. This study aimed to identify suitable drug–polymer–plasticizer systems for TA using combined theoretical and experimental methods. Methods: Using Hansen solubility parameters, seven hot-melt extrusion (HME)-grade polymers and four plasticizers were initially screened for miscibility with TA. Based on Δδt values, four polymers—Eudragit® L100 (EUD), Parteck® MXP (PVA), Plasdone® S-630 (PVPVA), and Aquasolve™ AS-MG (HPMCAS)—along with triethyl citrate (TEC), were selected for experimental evaluation. Differential scanning calorimetry, thermogravimetric analysis, and Fourier transform infrared spectroscopy assessed thermal behavior, miscibility, and chemical compatibility. Results: Amorphous TA content was highest with EUD (81.1%), followed by PVA (67.5%), PVPVA (45.6%), and HPMCAS (8.5%). Thermal incompatibility and TEC evaporation were observed in PVA, PVPVA, and HPMCAS systems. FTIR suggested TEC should be avoided in melt-based formulations with PVA and PVPVA due to PVA degradation and partial TA oxidation. No significant interactions were detected in HPMCAS samples heated to 220 °C, aligning with theoretical predictions. In contrast, the EUD–TEC system showed limited chemical reactivity and maintained TA’s structural integrity. Infrared bands at 1758 and 1802 cm−1 indicated minor anhydride formation above 160 °C with partial TEC evaporation. Conclusions: EUD/TEC were identified as a promising combination for the HME processing of TA. This work supports the rational formulation of stable amorphous systems for thermolabile drugs with poor solubility.